The Effect of Fintech Loans on Commercial Bank Margin - Afnizal Zulfan Ariffandi; Irwan Trinugroho (Jurnal Keuangan dan Perbankan, 2022)
This study aims to examine how far competition between commercial banks and fintech firms impacts the margins of commercial banks in Indonesia. Panel data regression analysis using the random-effects model was conducted on the financial data of 84 commercial banks from 2018 to 2021. This study found that the growth of fintech firms did not affect decreasing commercial banks’ margins. However, fintech loans’ growth was found to significantly and negatively effecting commercial banks’ margins, Meaning that fintech loans’ growth decreases the margins of commercial banks in Indonesia. Bank size, non-performing loan (NPL), and capital ratios do not significantly affect commercial banks’ margins. This research ultimately provides input for making fintech interest rate policies and also input for commercial banks to adopt technology so that they do not seem old-fashioned and convoluted. This research only examines the influence of fintech firms on commercial banks, so future research could examine the effect on different types of banks, such as Islamic banks and rural banks.